PENGOPTIMALISASIAN PERPUSTAKAAN DESA DALAM MENINGKATKAN BUDAYA BACA ANAK - Soleha Soleha (Scientia: Jurnal Hasil Penelitian, 2016)
Books and libraries are the keys to social changes in broadening the human mind. By reading many people will know all the information in all fields. However, reading is not only done in limited time and place. As the development of technology moves so fast, especially in the field of communication, information can be accessed very easily through various kinds of social media. One of the most accessible places to get information is the library. Nowadays, almost every village has a library since the government conducts a village literacy program by establishing a Community Library. The book is a window to the world and reading is its key. People who love to read and have a good learning attitude considered as a society that will be able to adapt and compete in this globalisation era. The advancement of technology enables people to access information quickly and easily from a variety of fields. It requires people to have the ability to explore, acquire, select and manage information in a smart way. Hence community library is an alternative in the effort of enlightening and educating people.